Pengaruh Perhatian Orangtua dalam Pembelajaran daring terhadap Motivasi Belajar Peserta Didik Madrasah Tsanawiyah - Maptuhah Maptuhah; Juhji Juhji (Program Studi PGMI STAI Daruttaqwa Gresik, 2021)
This study aims to analyze the influence of parental attention on students learning motivation in online learning during the covid-19 pandemic. The research method uses a quantitative approach. As many as 30 madrasah Tsanawiyah children aged 13-16 years were sampled in the study, they were given 20 questions related to learning motivation and parental attention. The selection of samples was conducted randomly in the pabuaran sub-district of Serang Regency, Banten Province in 2021. This study uses descriptive quantitative methods. Research instruments using questionnaires through Google Form. The data analysis method is done with the help of a computer software application program, SPSS 25 for windows. From the results of the data analysis known regression equation Y = 11.075 + 0.696. While the results of the T test obtained the results of the provisions of the Jubilee for df = 28 with an error rate of 0.05 or 5% is 1,701. While Thitung obtained from this study showed a value of 4,140. Because t hitung > t table = 4,140 > 1,701 ha was accepted and H0 was rejected. And the results of the calculation of determination test obtained the number R² of 0.380 or 38%. This indicates that the percentage influence of independent variables affects dependent variables by 38% while the rest by (100-38% = 62%) influenced by other variables or indicators not studied in this study. Thus, the results of the study concluded the influence of parental attention to the motivation of learning madrasah Tsanawiyah students in the district pabuaran Serang Banten Province. This study recommends parents to pay more attention to the child so that the child's learning motivation increases.